2003
DOI: 10.1076/ceyr.26.3.151.14893
|View full text |Cite
|
Sign up to set email alerts
|

Novel dipeptide prodrugs of acyclovir for ocular herpes infections: Bioreversion, antiviral activity and transport across rabbit cornea

Abstract: The dipeptide prodrugs were found to be more permeable than the parent drug, ACV. More permeable, less cytotoxic ACV dipeptide prodrugs exhibited excellent chemical stability and antiviral activity against herpes simplex virus thereby rendering these lead compounds promising drug candidates against herpes virus infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 13 publications
0
68
1
Order By: Relevance
“…The increase in the stability on incorporation of D-valine may be attributed to reduced affinity toward hydrolytic enzymes. Previous reports from Anand et al 10 clearly explained the bioconversion mechanism of dipeptide prodrugs. The dipeptide bond is hydrolyzed by the peptidases resulting in the regeneration of amino acid ester of ACV, which is further hydrolyzed by esterases regenerating the parent ACV.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The increase in the stability on incorporation of D-valine may be attributed to reduced affinity toward hydrolytic enzymes. Previous reports from Anand et al 10 clearly explained the bioconversion mechanism of dipeptide prodrugs. The dipeptide bond is hydrolyzed by the peptidases resulting in the regeneration of amino acid ester of ACV, which is further hydrolyzed by esterases regenerating the parent ACV.…”
Section: Discussionmentioning
confidence: 91%
“…9 These dipeptide prodrugs (GVACV and VVACV) were found to be more permeable due to specific targeting toward PEPT and are considered as the potential candidates for the treatment of ocular HSV infections. 10 …”
Section: Introductionmentioning
confidence: 99%
“…However, one of the major problems associated with these drugs is their poor ocular absorption, cytotoxicity, and mutagenicity, restricting their use in long-term treatment. Although the utility of valacyclovir against oral and genital herpes infections is well established and well documented (Fleming et al, 1997), it has not been used for topical application against ocular herpes infection, herpes simplex virus keratitis, probably due to a short half-life of Ļ³72 h in pH 5.6 (Anand et al, 2002b). Various lipophilic prodrugs of nucleoside analog acyclovir have been studied for improved ocular absorption (Hughes and Mitra, 1993) to cure HSV keratitis.…”
mentioning
confidence: 99%
“…Moreover, results obtained from this study are consistent with those observed for stereoisomeric prodrugs of saquinavir and acyclovir (32,33). Dipeptide prodrugs of acyclovir and ganciclovir have displayed significant improvements in transcorneal permeability relative to unmodified parent drugs (23,25,26,29,45). Half-lives displayed by LLACV, LDACV, and DLACV in intestinal homogenates are <0.08, 1, and 6 h, respectively.…”
Section: Cellular Uptake Studiesmentioning
confidence: 99%